Impact of geriatric nutritional risk index and diabetes mellitus on prognosis in ischaemic heart failure with reduced ejection fraction - Zhiyong Shi; Mingkai Yun; Haiyan Liu; Sijin Li; Xiaoli Zhang (Scientific Reports)
Abstract It is unclear whether diabetes mellitus (DM) affects the role of malnutrition in heart failure (HF). We evaluated the effect of the geriatric nutritional risk index (GNRI) on HF prognosis and DM’s role in this relationship. This single-centre retrospective cohort study included 540 HF patients with nutritional data grouped by DM status and GNRI score. The primary endpoint was all-cause mortality. Eighty-four patients (15.6%) were classified as malnourished (GNRI ≤ 98). Over a median follow-up of 4.0 years, 102 patients died. The DM/low GNRI (L-GNRI) group had the highest risk of all-cause death (HRadj: 3.253, 95% CI 1.643–6.474, P < 0.001) and cardiac death (HRadj: 3.411, 95% CI 1.606–7.243, P < 0.001) compared to the non-DM/high GNRI group. The adverse impact of L-GNRI was more pronounced in DM than in non-DM patients (P interaction < 0.05). In the total population and DM subgroup, GNRI was independently associated with an increased risk of all-cause and cardiac death after adjustment (all P < 0.05). In patients with DM, the GNRI classification significantly enhanced the predictive value of the model (all P < 0.05). A negative correlation between GNRI and HbA1c was observed only in patients with DM. Patients with HF with DM and malnutrition had the poorest prognosis. Poor glycemic control is related to increased malnutrition risk.